Morocco’s Makhzen and the Challenge of National Development - Zakaria Fatih (Journal of Global Initiatives, 2019)
This article explores the question of national development in Morocco considering the institution of the makhzen. It asserts that to adequately assess Morocco’s national development as a post-colonial country, it is necessary to rely on an economic model based in politics rather than in theories exclusively informed by classical and neoclassical economics. Among the key economists called upon to investigate the validity of politics in discussions of national development and income inequality are the following: Simon Kuznets, Thomas Piketty, W. A. Lewis, and the duo Daron Acemoglu and James A. Robinson, all of whom continue a long tradition of economic sociology that had been established by George Simmel, Max Weber, Emile Durkheim, and Thorstein Veblen. Acemoglu and Robinson offer an especially useful theoretical model to discuss Morocco in light of its pervasive political institution: the makhzen. Overall, the paper demonstrates that inadequate national institutions, such as the makhzen in the case of Morocco, adversely impact national development and increase the level of income inequality.